1996
DOI: 10.3109/10715769609149065
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Yield and the Antioxidant Defense System in Tomatoes Grown Under Heat Stress

Abstract: Four putative heat-tolerant tomato (Lycopersicum esculentum) cultivars (Tamasabro, Heat Wave, LHT-24, and Solar Set) and one putative heat-sensitive tomato cultivar (Floradade) were grown in the field under non-stress (average daily temperature of 26 degrees C) and heat-stress (average daily temperature of 34 degrees C) conditions. At anthesis, approximately five weeks after being transplanted to the field, leaf samples were collected for antioxidant analyses. Yield was determined by harvesting ripe fruit seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
25
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 53 publications
8
25
1
Order By: Relevance
“…Further, increase in GR can be directly corroborated with APX in concordance with the Halliwel-Asada pathway. This result is supported by the findings of Rainwater et al (1996) in heat tolerant tomato (Lycopersicum esculentum). In contrast to the above CAT, APX, and GR showed decreased activity on subjecting wild type organism to Cu 2?…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Further, increase in GR can be directly corroborated with APX in concordance with the Halliwel-Asada pathway. This result is supported by the findings of Rainwater et al (1996) in heat tolerant tomato (Lycopersicum esculentum). In contrast to the above CAT, APX, and GR showed decreased activity on subjecting wild type organism to Cu 2?…”
Section: Discussionsupporting
confidence: 80%
“…Besides, the enhanced activity of SOD in 47°C acclimated strain appears to be a requirement for the survival of the cell under high temperature when the rate of ROS production is high (Suzuki and Mittler 2006). These findings are supported by Rainwater et al (1996) in heat tolerant tomato (Lycopersicum esculentum) and by Sairam et al (2000) in wheat (Triticum aestivum). On the other hand on subjecting wild type organism to 50 lM Cu 2?…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have elucidated that heat stress alters the activity of antioxidant enzymes including SOD, CAT, APX, and POD in many plant species such as potato, tomato, wheat and mulberry (Rainwater and Gossett 1996, Sairam et al 2000, Chaitanya et al 2002, Vacca et al 2004. In this study, the activity of APX, CAT, POD and SOD in calli from both P. tangutica and tobacco increased rapidly under heat stress.…”
Section: Resultssupporting
confidence: 50%
“…Previous studies have elucidated the importance of maintaining a favorable antioxidative level in plant adaptation to heat stress (Rainwater et al 1996, Sairam et al 2000, Chaitanya et al 2002, Vacca et al 2004. The aim of the present study is to investigate the roles of G6PDH in mediating intracellular redox homeostasis in calli from P. tangutica and tobacco under heat stress.…”
Section: Resultsmentioning
confidence: 89%
“…High temperature stress of 35°C caused increase in SOD activity and decrease in activity of CAT, POX, APX, dehydroascorbate reductase and GR and increased levels of antioxidant compounds (Rivero et al 2004). Rainwater et al (1996) and Rivero et al (2004) reported that mild temperature stress increases the activity of antioxidant enzymes to cope up with the initial temperature stress.…”
mentioning
confidence: 99%